Pengaruh Kepemimpinan Situasional dan Budaya Organisasi Terhadap Kinerja Guru Dimediasi dengan Kepuasan Kerja - Muhammad Khairul Razikin; Bayu Sumantri; Adam Trifan; Muhammad Habibie (Inovatif: Jurnal Ekonomi, Manajemen, Akuntansi, Bisnis Digital dan Kewirausahaan, 2023)
This study aims to determine the measurement of the influence of situational leadership and organizational culture on teacher performance mediated by job satisfaction. The research method used is a quantitative method with a case study approach. The research results show that based on the results of the research that has been carried out, hypothesis 1 and hypothesis 5 are accepted. From the Path Coefision that has been obtained for the four variables, there are two variables that have a significant influence, there are two variables that have a significant influence. For the p-Values obtained from the four variables, there are 2 variables with the conclusion that there are 2 variables that can be used as adaptations of teacher performance measurement parameters.